History of bioethics in professional nursing education: a spanish view - Losa Iglesias, Marta Elena; Becerro de Bengoa Vallejo, Ricardo (Acta Bioethica, 2013)
Nursing education and the nursing profession must go hand by hand to emphasize efforts to improve knowledge in ethical decision-making and professional deontology. The nursing profession in Spain has struggled for legislation of the profession as well as a professional code of ethics. Based on the ethical specifications for nursing practice, it is evident that education in nursing ethics is of the most importance and should be emphasized as an integral component of higher-level nursing education. Nursing schools should seek to establish programs that effectively integrate the humanities with the biotechnological aspects of the profession and define strategies for monitoring nursing professionals who graduate from those schools.